Association between schizophrenia polygenic risk and neural correlates of emotion perception. (30th June 2018) - Dzafic, Ilvana; Burianová, Hana; Periyasamy, Sathish; Mowry, Bryan
Highlights: Influence of schizophrenia polygenic risk on brain during emotion perception. Greater genetic risk is associated with increased emotion regulation brain activity. Increased brain activity occurs during threatening emotion perception. Over-recruitment of emotion regulatory regions may be compensatory. Abstract: The neural correlates of emotion perception have been shown to be significantly altered in schizophrenia (SCZ) patients as well as their healthy relatives, possibly reflecting genetic susceptibility to the disease. The aim of the study was to investigate the association between SCZ polygenic risk and brain activity whilst testing perception of multisensory, dynamic emotional stimuli. We created SCZ polygenic risk scores (PRS) for a sample of twenty-eight healthy individuals. The PRS was based on data from the Psychiatric Genomics Consortium and was used as a regressor score in the neuroimaging analysis. The results of a multivariate brain-behaviour analysis show that higher SCZ PRS are related to increased activity in brain regions critical for emotion during the perception of threatening (angry) emotions. These results suggest that individuals with higher SCZ PRS over-activate the neural correlates underlying emotion during perception of threat, perhaps due to an increased experience of fear or neural inefficiency in emotion-regulation areas. Moreover, over-recruitment of emotion regulation regions might function as a compensation to maintain normal emotion regulation during threat perception. If replicated in larger studies, these findings may have important implications for understanding the neurophysiological biomarkers relevant in SCZ.